No ordinary company: Arnhem Land Fire Abatement (Northern Territory) Limited. Issue 4 (1st October 2020) - Altman, Jon; Ansell, Jennifer; Yibarbuk, Dean
ABSTRACT: Arnhem Land Fire Abatement (Northern Territory) Limited (ALFA) is a non-profit company established to make a financial return from savanna fire management. It operates as a charitable entity to ensure that its earnings benefit the Aboriginal landowners of Arnhem Land, many living in deep poverty. ALFA is unusual because it must operate at the intersection of Western and customary domains. It catalyses and supports the carbon emission avoidance activities of Aboriginal ranger groups and traditional landowners, who deploy customary and Western fire-management approaches at a large regional scale. Simultaneously, ALFA manages the Australian Carbon Credit Units that it earns, either selling them under contract to the Australian government or to corporate purchasers, or saving them for later sale. In this article we examine the first five years of ALFA since its establishment in 2015 – its origins and more recent history, its achievements and its governance. We then examine several climatic, financial, environmental and politico-cultural challenges that it faces operating in the Australian carbon and conservation economies. We show from diverse perspectives how, during a late-capitalist period of extreme climatic uncertainty, ALFA has evolved into an established model of sustainable postcolonial possibility, as 'no ordinary' company.